Cenozoic history of the Australian Monsoon - Stephen J. Gallagher; Vera A. Korasidis; Gerald Auer; David De Vleeschouwer; Jeroen Groeneveld; Beth Christensen (Progress in Earth and Planetary Science)
Abstract The Australian monsoon is part of the global monsoon and often included as a component of the Asian Monsoon system although they operate out of phase. Due to their hemispheric positions, the dry (wet) Australian winter (summer) monsoon coincides with the wet summer Asian monsoon and vice versa. The Australian monsoon controls rainfall distribution in northern tropical Australia where over 80% of the median annular rainfall occurs from December to March, the summer wet season. Three types of the Australian monsoon are distinguished based on distinct atmospheric circulation and heating patterns: a northwest Pseudo-Monsoon, a northeast Quasi-Monsoon and an Australian Monsoon (sensu stricto) north of Australia. While the modern climatology of the Australian monsoon has been extensively documented, its paleohistory is poorly constrained, especially in Australia’s continental interior where harsh arid climatic conditions have degraded almost all physical evidence of monsoonal activity. However, reassessment of northern and central Australian terrestrial and marine sequences reveals a fairly robust Cenozoic history of this monsoon, especially for the Neogene, which we synthesize for the first time here. Evidence for a Paleogene Australian paleomonsoon is equivocal due to the small number of sites, their limited age control, and the poor preservation of flora with ambiguous affinities. Modeling and tectonic evidence suggest the northern part of the Australian Plate migrated to the (sub)tropical region (north of 30°S) creating “modern” boundary conditions for monsoonal onset by ~10 Ma. Cores off northwest Australia reveal arid late Miocene and humid Pliocene conditions were followed by the Pseudo-Monsoon at ~3.5 Ma when northern hemisphere glacial expansion “forced” the ITCZ (Inter Tropical Convergent Zone) south. Subsequently, variable humid and arid periods typify Quaternary high-amplitude glacio-eustatic cycles until ~1 Ma, when arid conditions expanded across Australia. Glacial/interglacial cyclicity and obliquity/precession insolation during terminations modulated Pseudo-Monsoon intensity when the ITCZ migrated northward (during glacial) and southward (during interglacial periods) from ~1 Ma to present. From ~1.6 to 1 Ma, precession paced Pseudo-Monsoon variability. Mega-lake expansion in central Australia and fluvial intensification generally correspond to wetter interglacial periods. Lake Eyre monsoonal shorelines may have been influenced by abrupt millennial events. Monsoonal conditions re-established near the base of Holocene as the ITCZ migrated across northern Australia. The Australian Monsoon (sensu stricto) and Quasi-Monsoon (a) initiated from 12.5 to 11 ka; (b) intensifying from 9 to 2 ka; then (c) weakened, possibly due to the onset of ENSO intensification. The Pseudo-Monsoon was established at ~14.5 ka off northwest Australia intensifying from 11.5 to 7 ka. It weakened after ~7 ka north of 15°S and ~5 ka to the south. In the absence of a topographic influence, insolation (precession/obliquity), abrupt millennial events and/or ITCZ variability across northern Australia were important controls on Quaternary Australian monsoon intensity. Further investigations of deeper time pre-Quaternary records off northwest and northeast Australia will reveal the paleohistory of this important domain of the Global Monsoon.